Can teaching staff about the neurobiological underpinnings of borderline personality disorder instigate attitudinal change?. (3rd July 2014) - Clark, Charlotte J.; Fox, Emily; Long, Clive G.
Abstract: Background: There is an abundant literature on the unfavourable attitudes held by staff working in mental health care settings towards patients with borderline personality disorder. The aim of this study was to assess whether attendance at a training session about the neurobiological underpinnings of borderline personality disorder could improve knowledge and produce positive attitudinal change within staff members working in a low secure inpatient setting. Method: Staff knowledge and attitudes (Mental Health Locus of Origin, Empathic Concern and Perspective Taking) were assessed at baseline, post-training attendance and at an eight-week follow up. Results: Attendance at the training session was associated with significant increases in theoretical knowledge, Perspective Taking and Locus of Origin scores. However, there were no changes observed in Empathic Concern scores. Conclusion: This research suggests that a relatively brief training session, that utilises the neurobiological framework, can be effective in facilitating knowledge and attitudinal change for those working with borderline personality disorder. The implications of the findings are discussed along with suggestions for further research.